Batik sebagai simbol identitas dan persatuan nasional - Kirom, muhammad Misbahul (Maliki Interdisciplinary Journal, 2025)
Batik is an intangible cultural heritage of Indonesia that has been recognized worldwide and has an important role in forming and strengthening national identity. This study aims to examine the symbolic meaning of batik as a representation of cultural identity as well as an element that unites the nation amidst the diversity of ethnicities and cultures in Indonesia. Using a descriptive qualitative approach, this study analyzes various batik motifs from several regions and the role of batik in national events and the social life of the community. The results of the study show that batik not only reflects local values ​​and the philosophy of life of the local community, but also becomes a medium for expressing nationalism and social solidarity. Batik is able to bridge differences and strengthen a sense of togetherness within the framework of the Unitary State of the Republic of Indonesia. Therefore, the preservation and strengthening of the symbolic values ​​of batik are important in efforts to maintain the integrity of the nation and strengthen national identity.